Airborne microplastics: a comprehensive analysis of indoor and outdoor pollution patterns - Mina Rahmani; Fatemeh Yousefian; Fatameh Atoof; Sahar Gholipour; Zahra Batooli; Mansour Baziar; Nezam Mirzaei (Reviews on Environmental Health, 2026)
Abstract In recent decades, airborne microplastics (MPs) and nano plastics have emerged as critical environmental pollutants, posing potential human health risks including respiratory issues such as asthma, alveolitis, and chronic bronchitis. This systematic review and meta-analysis investigated the distribution, characteristics and concentrations of airborne MPs in indoor and outdoor environments based on studies published up to October 2023. Following PRISMA guidelines, 27 eligible studies across 16 countries were selected, with 21 providing sufficient quantitative data for meta-analysis. Due to extreme, robust heterogeneity across the studies (I 2 >99 %), a random-effects model was applied. Sensitivity analyses confirmed these findings were stable and not driven by individual outliers. The results demonstrated that indoor environments were more polluted than outdoor settings. For example, moderately polluted indoor environments exhibited mean concentrations of 1,380.28 MP/m 3 compared to 102.45 MP/m 3 outdoors. However, these findings are presented as a descriptive summary of the literature to highlight methodological variability. Consistent with this, moderator analyses revealed that the most significant contributor to inter-study variability was the type of detection instrument used, with FTIR consistently reporting higher concentrations than microscopy or Raman spectroscopy. Sampling duration also significantly influenced the results. Additionally, indoor healthcare centers and outdoor urban areas were identified as the most heavily contaminated sub-environments. These findings highlight the urgent need for standardized sampling and detection protocols, while emphasizing the critical importance of monitoring and mitigating indoor air quality to reduce human exposure to airborne MPs.